Why do cloud providers prefer renting to selling? A supply side perspective - Chieko Fujisawa; Norihiro Kasuga (International Telecommunications Society (ITS), 2019)
Expansion of the cloud computing market, a major reform in information and communication technology (ICT), has attracted wide attention. From the perspective of companies that need cloud services, if access to cloud spreads is available on rent instead of sales, initial investment cost will decline and the number of companies currently adopting the cloud system in the form of renting servers will increase. From the supply side perspective, what are the advantages of renting cloud services? To analyze this question, we consider a duopoly cloud market under licensing and examine the optimal strategy for providers. We find that in a two-part licensing contract, which includes high royalty and fixed fee charged upfront, when the cost-saving effect is high, both firms prefer renting to increase their revenue, but when the effect is low, each firm makes a different choice.
Keywords: D43; L13; L68; 330; Durable goods; Licensing contract; Selling; Renting; Cloud market